Thermodynamics and activity coefficients at infinite dilution for organic compounds and water in the ionic liquid 1-butyl-3-methylimidazolium perchlorate. (December 2017) - Chen, Jin-Yuan; Jiang, Hong-Xu; Liu, Jun-Ling; Jia, Hai-Xia; Jiao, Yu-Hai; Ge, Ming-Lan; Kang, Rong-Xue; Peng, Xiao-Ming; Xiong, Jie-Ming
Graphical abstract: Highlights: Measurements of activity coefficients at infinite dilution using GLC. The (gas-liquid) partition coefficients were calculated. The excess thermodynamic functions, entropies, and Gibbs energies were calculated. The solubility parameter of the IL [BMIM][ClO4 ] was determined. Selectivity and capacity for hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). Abstract: Activity coefficients at infinite dilution ( γ i ∞ ) and (gas–liquid) partition coefficients ( K L ) for organic compounds (alkanes, alkenes, alkyl benzenes, acetonitrile, acetone, tetrahydrofuran, ethyl acetate, 1, 4-dioxane, chloromethanes, and alcohols) and water in the ionic liquid (IL) 1-butyl-3-methylimidazolium perchlorate ([BMIM][ClO4 ]) have been measured by the (gas-liquid) chromatographic method in the temperature range of (303.15–353.15) K. Density, ρ as a function of temperature for [BMIM][ClO4 ] at pressure p = 101.3 kPa were measured. The values of the partial molar excess enthalpies at infinite dilution ( H ¯ i E, ∞ ) were derived from the temperature dependence of the γ i ∞ values. The entropies ( T ref S ¯ i E, ∞ ) and Gibbs free energies ( G ¯ i E, ∞ ) of organic solutes in [BMIM][ClO4 ] at a reference temperature T ref = 298.15 K were also calculated from the γ i ∞ values. The Hildebrand's solubility parameters of the IL [BMIM][ClO4 ] were also determined by the regular solution theory (RST) combined with Flory ''combinatorial'' equation. Selectivity ( S ij ∞ ) and capacity ( k j ∞ ) at infinite dilution at 323.15 K have been determined for n-hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j )). The results were analyzed in comparison to literature values for 1-buthyl-3-methylimidazolium-based ionic liquids (ILs) for the same separation problems. For three isomeric xylenes separation problems, selectivity at 323.15 K were also obtained from the γ i ∞ values.